PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 008 SUNGAI SEGAJAH KECAMATAN KUBU - ', Sugiati; ', Zulkifli; ', Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The background ofthis research is a learning process is still dominatedby the fourth grade teachers so that students become passive, as well as thematerials used by teachers and learning outcomes are not satisfactory value -value - average under KKM. The researchers aimed to determine the presence orabsence of the influence of problem-based learning models, both individually andclassically there is a class IV student learning outcomes in social studies in theelementary school of 008 River Segajah Kubu district. This study was conductedon 31 students of this data to the data collected through observation of problembasedlearning model through UAS I and UAS II for student learning outcomesdata classically before action with - average class of 58, while the daily test cycleI with - average 63 , 3 and cycle II was increased to 68.3, the activity of theteacher in the learning process of the first cycle of the first meeting of the 70increased at the second meeting to 85 and the second cycle meeting activity 4 90to 95 students the first cycle of the first meeting of 70 increased at the meeting to2 to 80 and the second cycle 4 meeting at the sixth meeting menigkat 85 to 95..Keywords: Problem Based Learning, IPS Learning Outcomes